2021
DOI: 10.3390/ijms22073697
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Use of Both Epigenetic and Non-Epigenetic Mechanisms to Efficiently Reactivate HIV Latency

Abstract: The persistence of latent HIV provirus pools in different resting CD4+ cell subsets remains the greatest obstacle in the current efforts to treat and cure HIV infection. Recent efforts to purge out latently infected memory CD4+ T-cells using latency-reversing agents have failed in clinical trials. This review discusses the epigenetic and non-epigenetic mechanisms of HIV latency control, major limitations of the current approaches of using latency-reversing agents to reactivate HIV latency in resting CD4+ T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The resultant complex formed is made up of multiple proteins comprising TBP and TAF, referred to as TFIID, which, along with three SP1 binding sites, constitutes the minimal transcription complex that can induce basal HIV LTR promoter transcription. However, for efficient HIV LTR promoter-mediated transcription, it requires the TFIID interaction with upstream enhancer binding factors such as NF-κB, AP-1 or NFAT [75,[82][83][84][85][86][87][88][89][90]. Transcription factor II H (TFIIH) exhibits kinase activity (CDK7) required for promoter clearance by phosphorylating the C-terminal domain (CTD) of RNAP II, whose recruitment to the HIV LTR promoter is reported to be the major determinant in HIV transcription, especially HIV-1 transcription initiation [80,91,92].…”
Section: Transcriptionmentioning
confidence: 99%
“…The resultant complex formed is made up of multiple proteins comprising TBP and TAF, referred to as TFIID, which, along with three SP1 binding sites, constitutes the minimal transcription complex that can induce basal HIV LTR promoter transcription. However, for efficient HIV LTR promoter-mediated transcription, it requires the TFIID interaction with upstream enhancer binding factors such as NF-κB, AP-1 or NFAT [75,[82][83][84][85][86][87][88][89][90]. Transcription factor II H (TFIIH) exhibits kinase activity (CDK7) required for promoter clearance by phosphorylating the C-terminal domain (CTD) of RNAP II, whose recruitment to the HIV LTR promoter is reported to be the major determinant in HIV transcription, especially HIV-1 transcription initiation [80,91,92].…”
Section: Transcriptionmentioning
confidence: 99%
“…The latent HIV provirus, the hallmark of HIV latency, is integrated viral DNA that is transcriptionally silent and cannot be reached by the current combination antiretroviral therapy (cART), thus posing a great obstacle to the treatment and cure of HIV infection [37][38][39][40][41][42][43][44]. Attempts to cure HIV infection in patients undergoing cART require the effective targeting of all possible viral reservoirs in all anatomical sites.…”
Section: Hiv Latency In the Cnsmentioning
confidence: 99%
“…Recent evidence has shown that unintegrated HIV can also produce viral proteins, which exacerbate the host immune response and lead to excessive toxicity and cell death [9]. Hence, to make ART more effective, research efforts have been diverted to identify the mechanisms through which latent HIV can be reactivated before being targeted by antiretrovirals [9][10][11][12][13]. Latency reversal agents such as romidepsin, JQ-1, and panobinostat have effectively reactivated the peripheral latent viral reservoir.…”
Section: Introductionmentioning
confidence: 99%